(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Proteinuria is the most reliable marker of diabetic nephropathy and an index of atherosclerosis and cardiovascular mortality in diabetic patients. In addition, common carotid artery intima-media thickness (CIMT) is a sensitive marker of early atherosclerosis and cardiovascular risk. The aim of this study was to evaluate the association between proteinuria and CIMT in type 2 diabetic patients. Materials and Methods. In a cross-sectional study, 154 patients with type 2 diabetes mellitus were enrolled. The CIMT was measured for all of the patients by one researcher. The 24-hour urine protein was measured using trichloroacetic acid method. Results. A total of 154 type 2 diabetic patients were enrolled with a mean diabetes mellitus duration of 8.91 ± 6.99 years (95 women and 55 men). The mean urinary protein in the patients was 294.70 ± 525.85 mg/24 h. The mean CIMT in all of the patients was 0.84 ± 0.19 mm, and it was greater in the men than in the women (P = .03). The CIMT significantly correlated with patients’ age (P < .001), systolic blood pressure (P < .001), and urinary protein excretion (P = .001). There was a marginal positive correlation between diabetes mellitus duration and the CIMT (P = .049). Conclusions. This study showed a significant association between CIMT, as a sensitive marker of macrovascular complication of diabetes mellitus, and proteinuria as an important index of microvascular complication of the disease.